E-Learning and Understanding of Accounting During Covid-19 Pandemic - Sigit Hermawan; Nur Ravita Hanun; M Ilyas Junjunan (Universitas Pendidikan Ganesha, 2021)
Covid-19 Pandemic has taken place throughout the world and has changed the whole structure of life including the fields of business education and accounting. This study was designed to analyze various factors that cause accounting understanding in the Covid-19 Pandemic. Some of these factors are emotional intelligence, availability of technological facilities, and implementation of e learning. The study was conducted during the Covid-19 Pandemic period, namely in April and May 2020 by distributing questionnaires to accounting students amounting to 194 as a research sample. Based on the results of the study, Emotional Intelligence and E-Learning implementation affect accounting understanding. However, the availability of information technology partially has no effect on the understanding of its accounting. With the results of this study will have implications for various policies related to learning in business and accounting during the Covid-19 Pandemic, especially on the availability of information technology and implementation of e learning.